ANALISIS PENERAPAN BUSINESS INTELLIGENCE DALAM TREN PASAR DENGAN COBIT 2019 - Maharani, Annisa; Maulana, Haisyam; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
ABSTRACT This study examines the implementation of Business Intelligence (BI) for market trend analysis at PT. Asia Tritunggal Jaya by applying the COBIT 2019 framework. The main issue faced by the company lies in the lack of structured data management, which hinders effective decision- making. The study aims to evaluate database management, develop BI-based data visualizations, and assess BI governance maturity using COBIT 2019. A descriptive case study was conducted over seven months, involving interviews, observations, and internal documentation. Data were processed using ETL techniques, with K-Means Clustering applied to analyze customer purchasing patterns, while Power BI was employed to create interactive dashboards. The BI governance assessment referred to APO, BAI, and DSS domains of COBIT 2019. Findings reveal that although the company has structured transactional records, database management remains suboptimal. Power BI visualization effectively presented sales and market insights. COBIT 2019 evaluation placed BI governance at Level 2 (Managed), indicating that processes are in place but not yet fully standardized. In conclusion, BI has supported market trend analysis and decision-making, but improvements in governance and standardization are still required for long-term effectiveness.